Sociolect Variations in the Utterances Of Rural and Urban Communities: A Case Study in Cisata District and Pandeglang City - Haryani, Siti; Siva, Wina; Idham P. P, Teris; Fadli, Naufal; Ramdhan, Andi; Julianti, Ulfah (Jurnal Multidisiplin Sahombu, 2025)
This study investigates sociolect variation in the speech of rural and urban communities, focusing on Cisata District and Pandeglang City, Banten Province. Using a qualitative-descriptive approach with the ethnography of communication method, the research explores how language use is shaped by education, age, occupation, and location. Data were collected through observations and interviews with selected informants in both areas. Analysis based on Labov’s and Fishman’s theories reveals clear distinctions: rural speakers use Sundanese dialects and informal Indonesian, reflecting traditional lifestyles, while urban speakers prefer standard or semi-formal Indonesian with frequent code-mixing, especially among youth and the educated. The findings show that sociolect variation is influenced not only by geography but also by educational access and social interaction. This research highlights the role of urbanization in shaping language use while underlining the need to preserve local linguistic identities amid social change.